Rumah Kreatif (RK) Baubau's Successful Learning Methods For Speaking Performance - Hasrida Ardin; Nurhayati Nurhayati; Afianti Afianti (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
The purpose of this study was to outline the successful speaking performance learning techniques used by the Rumah Kreatif (RK) Baubau. The problem statement, "What effective learning strategies of speaking performance applied by Rumah Kreatif (RK) Baubau," served as its foundation.This sresearch used a case study methodology and qualitative research.This study uses interviews and observation as its instruments. Direct observation and structured interviews are the methods used to gather data. Based on information gathered from the researcher's observations of members of the Rumah Kreatif (RK) from June 23 to July 3, 2025, Baubau demonstrated that the Discussion method, Debate method, Presentation method, and Role Play method are effective learning strategies for speaking performance used by RK Because RK is an English-speaking organization in the city of Baubau, they joined with the intention of making friends and improving their English language proficiency, particularly in speaking.